Knowledge Mobilization of Methods and Findings of Intimate Partner Violence Research in Canada's North - Moffitt, Pertice M.; Fikowski, Heather (2017)
Event Theme: Influencing Global Health Through the Advancement of Nursing Scholarship Intimate partner violence (IPV) in Canada’s Northwest Territories (NWT) is a grave social and public health issue with rates of IPV nine times the national average (Statistics Canada, 2016). The social, contextual and cultural context including colonization (Kubik, Bourassa & Hampton, 2009), the intergenerational impact of Indian residential school (Bombay, Matheson & Anison, 2014; Elias et al., Mohatt et al., 2014), alcohol and substance use, and social determinants (poverty, housing, unemployment, gender) all factor into the high rates of IPV (Moffitt et al., 2013; Weurch et al.,2016). From 2011 to 2016, researchers conducted an investigation into “the Rural and Northern Community Response to Intimate Partner Violence”, funded by a Social Sciences and Humanities Research Council of Canada (SSHRC) and Community/University Research Alliance grant. The research questions are: What are the needs of women experiencing intimate partner violence? What are the gaps in services to meet these needs? How can we create and sustain nonviolent communities? Frontline service providers (n=56) were interviewed through individual interviews (n=44) and two focus groups (n=12). A grounded theory was generated through constant comparative methods identifying the central problem as “ our hands are tied .” The social processes that create this community response are three: putting up with violence; shutting up about violence; and, getting on with life. An action plan was created to address the problem of “ our hands are tied .” One of the tenets of the action plan expressed by frontline service providers was the salience of education and awareness to overcome the culture of violence and silence that is present in the territory. The purpose of this presentation is to highlight knowledge mobilization (a way of taking the knowledge generated by a study and putting it into action to afford change in a culturally and contextually congruent way) in relation to the research findings of this study and to specific strategies of knowledge mobilization used for our northern culture. Knowledge mobilization was conducted from the beginning of the research through to completion of the project and will extend beyond the completion date with dissemination of the findings. The process of knowledge mobilization occurred through a variety of different activities, some of which were related to the research methods and some activities were conducted in collaboration with a territorial activists’ group, the Coalition Against Family Violence, of which the researchers were active members. One of the unique methods that was used in year one of the study was geographical information system (GIS) maps to plot the incidents of IPV in the territory. At the same time as we gathered statistics from the federal policing agency, we conducted an environmental scan to illuminate the resources available for women in the territory (emergency shelters, victim services, police services, hospitals and health centers). Both data sets were accessed by geographers on our team to create a GIS map of “IPV Incidences and Resources”. The map provides a visual of the high number of IPV incidents in all communities of the NWT and in the gaps in services. This map was a tool for knowledge mobilization for the research team and also for public consumption when we were asked to speak during “family violence awareness week”. As well, as themes that emerged through data analyses, more ideas were generated to map (a comparison of seasonal distances to shelters; homicides in the territory and emergency protective orders). During this presentation, the GIS maps will be shared and their contribution to knowledge mobilization will be highlighted. In addition, examples of specific strategies that were used within our context included: Community Fairs in remote communities, Community Presentations and Dialogue with Frontline Service Providers and Safety School with Undergraduate Nursing and Social Work Students. Community fairs were sponsored by the territorial government as a way of bringing government and nongovernment agencies together to provide knowledge of resources available and health promotion of a variety of issues. During a community fair, we used a flyer written in plain language to translate our research findings to the community and response cards where community members had the opportunity to answer the question, “what can you and your community do to end violence?” The responses were both drawings by children and words by adults covering a variety of topics. Formal community presentations about the findings of the research and the action plan have been delivered to five communities targeting frontline service providers. Following the presentations, a facilitated conversation was conducted with the participants to encourage their feedback about what the findings and suggested actions. Safety school is a half-day class spent with undergraduate students to address violence in the territory and provide access to resources available for women. The safety school promotes sharing local resources and initiatives to enable knowledge translation with future frontline workers. It is no secret that there are higher rates of intimate partner violence throughout the North and in the Northwest Territories particularly. Working with service providers to mobilize the limits and challenges they face in alleviating suffering and eliminating violence in their communities is critical to developing collaborative and effective systems and programs. Education and awareness through informative presentations and campaigns and providing opportunities to reflect and create space for dialogue will assist in the transformation towards nonviolent communities.